Employment Equity in Canada: The Legacy of the Abella Report - Agócs, Carol (2014)
In the mid-1980s, the Abella Commission on Equality in Employment and the federal Employment Equity Act made Canada a policy leader in addressing systemic discrimination in the workplace. More than twenty-five years later, Employment Equity in Canada assembles a distinguished group of experts to examine the state of employment equity in Canada today. Examining the evidence of nearly thirty years, the contributors – both scholars and practitioners of employment policy – evaluate the history and influence of the Abella Report, the impact of Canada’s employment equity legislation on equality in the workplace, and the future of substantive equality in an environment where the Canadian government is increasingly hostile to intervention in the workplace. They compare Canada’s legal and policy choices to those of the United States and to the UN Convention on the Rights of Persons with Disabilities, and examine ways in which the concept of employment equity might be expanded to embrace other vulnerable communities. Their observations will be essential reading for those seeking to understand the past, present, and future of Canadian employment and equity policy. –Publisher's description.
OCLC: 911039794

French Canadians, Furs, and Indigenous Women in the Making of the Pacific Northwest - Barman, Jean (UBC Press, 2014)
In [this book], Jean Barman rewrites the history of the Pacific Northwest from the perspective of French Canadians involved in the fur economy, the indigenous women whose presence in their lives encouraged them to stay, and their descendants. Joined in this distant setting by Quebec paternal origins, the French language, and Catholicism, French Canadians comprised Canadians from Quebec, Iroquois from the Montreal area, and metis combining Canadian and indigenous descent. For half a century, French Canadians were the largest group of newcomers in this region extending from Oregon and Washington east into Montana and north through British Columbia. Here, they facilitated the early overland crossings, drove the fur economy, initiated non-wholly-indigenous agricultural settlement, eased relations with indigenous peoples, and ensured that, when the Pacific Northwest was divided in 1846, the northern half would go to Britain, giving today's Canada its Pacific shoreline. In the generations that followed, Barman argues, descendants did not become Metis, as the term has been used to describe a people apart, but rather drew on both their French Canadians and indigenous inheritances to make the best possible lives for themselves and those around them. –Publisher's description. Contents: Pt. 1. French Canadians And The Fur Economy. To Be French Canadian – Facilitating the Overland Crossings – Driving the Fur Economy – Deciding Whether to Go or to Stay. Pt. 2. French Canadians, Indigenous Women, And Family Life In The Fur Economy. Taking Indigenous Women Seriously – Innovating Family Life – Initiating Permanent Settlement – Saving British Columbia for Canada. Pt. 3. Beyond The Fur Economy. Negotiating Changing Times – Enabling Sons and Daughters – To Be French Canadian and Indigenous – Reclaiming the Past. Includes bibliographical references (pages 404-430) and index.
OCLC: 875520868
Keywords: Commerce; Fur trade; Histoire Femmes autochtones; Histoire Fourrures; Histoire Fur trade. Genre/Form: History; History Canadiens d'origine franaise; History Native women; History. French Canadians; Nord-Ouest; Cte (Amrique du Nord); Northwest; Pacific

Unions Matter: Advancing Democracy, Economic Equality, and Social Justice - Behrens, Matthew (Between the Lines, 2014)
Income inequality has risen rapidly over the past three decades. In Canada it is now at its highest level since 1928. One of the root causes: the consistent chipping away of labour rights. The labour movement has been left unable to maintain membership levels and incapable of narrowing the income gap through collective bargaining, with profound implications for Canadians. Labour rights are human rights. They provide a powerful democratic counterweight to the growing power of corporations and the wealthy, and are key to a functioning democracy. Unions Matter affirms the critical role that unions and strong labour rights play in creating greater economic equality and promoting the social wellbeing of all citizens. –Publisher's description
Keywords: Canada; Canadian Foundation for Labour Rights; Democracy; Employee rights; Equality; Labor movement; Labor unions; Social aspects; Social justice

Equality Deferred: Sex Discrimination and British Columbia's Human Rights State. - Clément, Dominique (UBC Press, 2014)
[This book] traces the history of sex discrimination in Canadian law and the origins of human rights legislation, demonstrating how governments inhibit the application of their own laws, and how it falls to social movements to create, promote, and enforce these laws. Focusing on British Columbia – the first jurisdiction to prohibit discrimination on the basis of sex – Clément documents a variety of absurd, almost unbelievable, acts of discrimination. The province was at the forefront of the women’s movement, which produced the country’s first rape crisis centres, first feminist newspaper, and first battered women’s shelters. And yet nowhere else in the country was human rights law more contested. For an entire generation, the province’s two dominant political parties fought to impose their respective vision of the human rights state. This history of human rights law, based on previously undisclosed records of British Columbia’s human rights commission, begins with the province’s first equal pay legislation in 1953 and ends with the collapse of the country’s most progressive human rights legal regime in 1984. This book is not only a testament to the revolutionary impact of human rights on Canadian law but also a reminder that it takes more than laws to effect transformative social change. –Publisher's description. Contents: Introduction – "No Jews or dogs allowed": anti-discrimination law – Gender and Canada's human rights state – Women and anti-discrimination law in British Columbia, 1953-69 – Jack Sherlock and the failed Human Rights Act, 1969-73 – Kathleen Ruff and the Human Rights Code, 1973-79 – Struggling to innovate, 1979-83 – Making new law under the Human Rights Code – The politics of (undermining) human rights : the Human Rights Act, 1983-84 – Conclusion.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/equalitydeferred0000clem OCLC: 902835706

Revolutionizing Retail: Workers, Political Action, and Social Change - Coulter, Kendra (Palgrave Macmillan, 2014)
Retail workers are a large labor force, yet their jobs are generally devalued and dominated by low wages, precarious conditions, and disrespect. Coulter draws on three years of comparative research on retail workers and political action, including fieldwork in Canada, the United States, and Sweden, to explore what is needed to improve workers' wellbeing and transform retail work. The only book of its kind, Revolutionizing Retail explains the strategies being used to improve retail jobs and retail workers' quality of life, including diverse forms of organizing, public policy, and good management. Coulter analyzes the degree to which current efforts are succeeding, and what lessons they offer about the present and future of work, forms of agency, and class, gender, and race relations. The power of culture, emotions, and workers' personal experiences of political action are at the heart of this engaging discussion of the challenges and possibilities of social change. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/revolutionizingr0000coul https://www.researchgate.net/publication/309415903_Revolutionizing_retail_Workers_political_action_and_social_change OCLC: 859253083
Keywords: Commerce de détail Personnel; Labor movement; Mouvement ouvrier; Retail trade Employees; Social change

Red Skin, White Masks: Rejecting the Colonial Politics of Recognition - Coulthard, Glen Sean (University of Minnesota Press, 2014)
Over the past forty years, recognition has become the dominant mode of negotiation and decolonization between the nation-state and Indigenous nations in North America. The term?recognition? shapes debates over Indigenous cultural distinctiveness, Indigenous rights to land and self-government, and Indigenous peoples' right to benefit from the development of their lands and resources. In a work of critically engaged political theory, Glen Sean Coulthard challenges recognition as a method of organizing difference and identity in liberal politics, questioning the assumption that contemporary difference and past histories of destructive colonialism between the state and Indigenous peoples can be reconciled through a process of acknowledgment. Beyond this, Coulthard examines an alternative politics–one that seeks to revalue, reconstruct, and redeploy Indigenous cultural practices based on self-recognition rather than on seeking appreciation from the very agents of colonialism. Coulthard demonstrates how a place-based modification of Karl Marx's theory of primitive accumulation throws light on Indigenous-state relations in settler-colonial contexts and how Frantz Fanon's critique of colonial recognition shows that this relationship reproduces itself over time. This framework strengthens his exploration of the ways that the politics of recognition has come to serve the interests of settler-colonial power. In addressing the core tenets of Indigenous resistance movements, like Red Power and Idle No More, Coulthard offers fresh insights into the politics of active decolonization. –Publisher's description.
Available at Internet Archive to readers with print disabilities: https://archive.org/details/redskinwhitemask0000coul OCLC: 875769300
Keywords: Canada; Canada. Ethnic relations; Canada. Indians; Treatment of; Canada. Native peoples; Government relations. Indians of North America; Government relations. Native peoples; Indians of North America; Legal status; laws; etc.; Legal status; laws; etc. Indians of North America; Political aspects. Indians of North America; Politics and government. Indians of North America; Politics and government. Indians; Treatment of. Indianerpolitik Rechtsstellung Indianer Selbstbestimmungsrecht Nordamerikas indianer; Politics and government. Native peoples; politiska aspekter

In Solidarity: Academic Librarian Labour Activism and Union Participation in Canada - Dekker, Jennifer; Kandiuk, Mary (Library Juice Press, 2014)
Provides a historical and current perspective regarding the unionization of academic librarians, an exploration of some of the major labour issues affecting academic librarians in a certified and non-certified union context,as well as case studies relating to the unionization of academic librarians at selected institutions in Canada. –Publisher's description
Keywords: Academic librarians; Canada; Collective bargaining; Faculty status; Labor Unions; Librarians' unions; Library employees

L'abbé Pierre Gravel, syndicaliste et ultranationaliste - Dumas, Alexandre (Septentrion, 2014)
Alors que le Québec est plongé dans la Grande Dépression, l'abbé Pierre Gravel promeut le syndicalisme dans l'industrie québécoise de l'amiante. Son discours radical et sévère à l'endroit des patrons tranche avec celui des autres prêtres qui oeuvrent dans le mouvement ouvrier. À l'aube de la Seconde Guerre mondiale, il encourage les Canadiens français à mener une révolution nationale en s'inspirant des dictateurs européens. Orateur aux idées sociales et nationales arrêtées et parfois dérangeantes, il fait face à l'opposition des gouvernements. Antisémite et ultranationaliste, ce réactionnaire prêche pourtant une doctrine sociale qui pouvait être considérée comme « communiste » à son époque et dont plusieurs éléments seront mis en place au cours de la Révolution tranquille, à commencer par la nationalisation de l'électricité. Comment peut-on concilier ces deux écoles de pensée à première vue contradictoires ? Peut-on être à la fois syndicaliste et fasciste ? Le parcours de l'abbé Pierre Gravel contribue à jeter un regard nouveau sur la droite nationaliste québécoise de cette époque tourmentée. –Publisher's description
OCLC: 901113156
Keywords: Biographies; Catholic Church; Catholic Church Clergy Biography; Clergy; Clergé Activité politique Canada 20e siècle; Gravel; Pierre; Gravel; Pierre; 1899-1977; Nationalisme et socialisme Canada Québec (Canada) (province) 20e siècle; Syndicalisme Canada Québec (Canada) (province) 20e siècle; Église catholique Clergé Biographies

Temporary Work, Agencies and Unfree Labour Insecurity in the New World of Work - Fudge, Judy; Strauss, Kendra (Routledge, Taylor & Francis Group, 2014)
Unfree labor has not disappeared from advanced capitalist economies. In this sense the debates among and between Marxist and orthodox economic historians about the incompatibility of capitalism and unfree labor are moot: the International Labour Organisation has identified forced, coerced, and unfree labor as a contemporary issue of global concern. Previously hidden forms of unfree labor have emerged in parallel with several other well-documented trends affecting labor conditions, rights, and modes of regulation. These evolving types of unfree labor include the increasing normalization of contingent work (and, by extension, the undermining of the standard contract of employment), and an increase in labor intermediation. The normative, political, and numerical rise of temporary employment agencies in many countries in the last three decades is indicative of these trends. It is in the context of this rapidly changing landscape that this book consolidates and expands on research designed to understand new institutions for work in the global era. This edited collection provides a theoretical and empirical exploration of the links between unfree labor, intermediation, and modes of regulation, with particular focus on the evolving institutional forms and political-economic contexts that have been implicated in, and shaped by, the ascendency of temp agencies. What is distinctive about this collection is this bi-focal lens: it makes a substantial theoretical contribution by linking disparate literatures on, and debates about, the co-evolution of contingent work and unfree labor, new forms of labor intermediation, and different regulatory approaches; but it further lays the foundation for this theory in a series of empirically rich and geographically diverse case studies. This integrative approach is grounded in a cross-national comparative framework, using this approach as the basis for assessing how, and to what extent, temporary agency work can be considered unfree wage labor. –Publisher's description
Keywords: Employment agencies; Job security; Labor market; Temporary employment

Trouble on Main Street: Mackenzie King, Reason, Race and the 1907 Vancouver Riots - Gilmour, Julie F. (Allen Lane, 2014)
The weather on Sept. 7, 1907 was hot and tempers were short. British Columbians had always been sensitive to Asian immigration and had become increasingly fearful over the summer. More Japanese immigrants were coming to B.C. and rumours smouldered of massive labour contracts for the projected Grand Trunk Pacific Railway.Like the citizens of Seattle and San Francisco, the residents of Vancouver had established a bipartisan Asiatic Exclusion League aimed at Japanese, Chinese, and South Asian immigrants in order to protect “White Canada.” The league had widespread support among trade union organizations and churches, and so a parade during the Labour Day weekend was scheduled. The result was a violent riot that drew the world’s attention to Vancouver, to Canadian immigration policy, and to Britain’s 1902 alliance with the Japanese. Historian Julie Gilmour traces the impact of these events on the life and work of future prime minister W.L. Mackenzie King, and on Canada’s relationships with Britain, the United States, China, Japan, and India. King’s involvement with the commissions set up to evaluate the damages incurred during the riots led to his interest in opium suppression and immigration control, and clarified his own sense of Canada’s role in the empire. Trouble on Main Street portrays a nation, and a time, at once relatively recent and shockingly unrecognizable. Over a century later, the links between local pressures, policy, and international events provide insight into current debates on terror, immigration, and Canadian security. – Publisher's description

Gender History: Canadian Perspectives - Keough, Willeen G.; Campbell, Lara A. (Oxford University Press, 2014)
Seamlessly integrating primary and secondary sources with insightful original overviews, Gender History: Canadian Perspectives is a comprehensive resource for students of gender history in Canada. This reader-textbook takes and innovative historical and thematic approach - the first half is chronological in structure, tracing developments from the pre-contacts such as work, the law, sexuality, religion, and popular culture. The result is a solid introduction to the broad patterns and themes of gender history in Canada, with particular emphasis on the diversity of gender experiences and the intersections of gender with class and race. –Publisher's description
https://www.sfu.ca/history/publications/2013-keough.html
Keywords: Sex role – Canada – History

Resources, Empire and Labour: Crisis, Lessons and Alternatives - Leadbeater, David (Fernwood, 2014)
The interconnections of natural resources, empire and labour run through the most central and conflict-ridden crises of our times: war, environmental degradation, impoverishment and plutocracy. Crucial to understand and to change the conditions that give rise to these crises is the critical study of resource development and, more broadly, the resources question, which is the subject of this volume. –Publisher's description.
http://fernwoodpublishing.ca/book/resources-empire-and-labour

The Raids: Nickel Range Trilogy - Lowe, Mick (Baraka Books, 2014)
It’s spring, 1963 in the “Nickel Capital of the World.” Nineteen-year-old Jake McCool is about to undergo a rite of passage—his first shift underground in a hard rock mine. But the Cold War is at its height, and Jake is also about to become a reluctant participant in a bitter interunion battle fueled by the global struggle between two ideologies in the wake of the Second World War. So is his girlfriend, Jo Ann Winters. Together the couple are swept up in a web of intrigue; at its center is a terrible secret that will haunt their relationship for the rest of their lives, as their hometown becomes not only one of the world’s greatest hard rock mining centers, but also the epicenter of the Cold War in North America. In this fast-paced novel set against the little-known historical backdrop of a true-life battle that included vicious beatings, riots, and worse, author Mick Lowe posits a provocative premise: that the U.S. government sponsored a ruthless covert operation to destabilize a strategic community in the heartland of its closest ally, Canada. –Publisher's description
Novel
Keywords: Blue-collar work; Cold War; Miners; Nickel mines and mining; Ontario Sudbury; Strategy

Hobohemia and the Crucifixion Machine: Rival Images of a New World in 1930s Vancouver - McCallum, Todd (AU Press, 2014)
In the early years of the Great Depression, thousands of unemployed homeless transients settled into Vancouver’s “hobo jungle.” The jungle operated as a distinct community, in which goods were exchanged and shared directly, without benefit of currency. The organization of life was immediate and consensual, conducted in the absence of capital accumulation. But as the transients moved from the jungles to the city, they made innumerable demands on Vancouver’s Relief Department, consuming financial resources at a rate that threatened the city with bankruptcy. In response, the municipality instituted a card-control system—no longer offering relief recipients currency to do with as they chose. It also implemented new investigative and assessment procedures, including office spies, to weed out organizational inefficiencies. McCallum argues that, threatened by this “ungovernable society,” Vancouver’s Relief Department employed Fordist management methods that ultimately stripped the transients of their individuality. Vancouver’s municipal government entered into contractual relationships with dozens of private businesses, tendering bids for meals in much the same fashion as for printing jobs and construction projects. As a result, entrepreneurs clamoured to get their share of the state spending. With the emergence of work relief camps, the provincial government harnessed the only currency that homeless men possessed: their muscle. This new form of unfree labour aided the province in developing its tourist driven “image” economy, as well as facilitating the transportation of natural resources and manufactured goods. It also led eventually to the most significant protest movement of 1930s’ Canada, the On-to-Ottawa Trek. Hobohemia and the Crucifixion Machine explores the connections between the history of transiency and that of Fordism, offering a new interpretation of the economic and political crises that wracked Canada in the early years of the Great Depression. –Publisher's description
Keywords: 1929; 20th century; British Columbia; Depressions; History; Public welfare; Services for; Services for. Unemployed; Social conditions; Transients; Relief of; Unemployed; Vancouver

Rebel Youth: 1960s Labour Unrest, Young Workers, and New Leftists in English Canada - Milligan, Ian (UBC Press, 2014)
During the "long sixties" - between 1964 and 1973 - baby boomers raised on democratic postwar ideals demanded a more egalitarian society for all. While a few became vocal leaders at universities across Canada, nearly 90% of Canada's young people went straight to work after high school. There, they brought the anti-authoritarian spirit of the youth revolt to the labour movement. While university-based activists combined youth culture with a new brand of radicalism to form the New Left, young workers were pressing for wildcat strikes and defying their aging union leaders in a wave of renewed militancy that swept the country. In Rebel Youth, Ian Milligan looks at these converging currents, demonstrating convincingly how they were part of a single youth phenomenon. With just short of seventy interviews complementing the extensive use of archival records, this book reveals a youth current that, despite regional differences, spanned an intellectual network from Halifax to Victoria that read the same publications, consulted the same thinkers, and found inspiration in the same shared ideas. Rebel Youth draws important connections between the stories of young workers and the youth movement in Canada, claiming a central place for labour and class in the legacy of this formative decade. –Publisher's description
OCLC: 865158388

Transformations des marchés du travail et innovations syndicales au Québec - Noiseux, Yanick (Presses de L'Université du Québec, 2014)
Pour qui s’intéresse à l’évolution du travail au Québec, le passage à un régime néolibéral au tournant des années 1980 renvoie à un concept : la flexibilisation. Trente ans plus tard, avec la montée en flèche du nombre d’emplois atypiques, force est de constater que flexibilité rime aussi avec précarité, l’emploi atypique se distinguant trop souvent par une moindre rémunération et un accès restreint aux multiples formes de protection sociale. Comment le syndicalisme peut-il s’ajuster aux besoins différenciés d’une main-d’œuvre de plus en plus diversifiée et employée sur des marchés du travail toujours plus segmentés ? L’auteur nous invite à penser le marché du travail à partir de sa périphérie, et à réfléchir à l’innovation syndicale à partir des pratiques, des stratégies et des revendications d’organisations de travailleurs se situant sur les marges de la société salariale. Dans une démarche qui vise le rajeunissement, voire la métamorphose du syndicalisme, il porte attention aux possibilités d’innovation sous-tendue par la nouvelle configuration du travail dans le capitalisme d’aujourd’hui. Pour ce faire, il présente un état des lieux du travail sur les marchés périphériques au Québec, en accordant une place prépondérante aux expériences des travailleurs, puis expose des pistes de réflexion sur le renouvellement de la théorie syndicale et sur le redéploiement de l’action syndicale au Québec. Enfin, il propose cinq études d’expériences portées, ici et maintenant, par des travailleurs atypiques et des organisations syndicales soucieuses de répondre à leurs besoins différenciés en matière d’organisation collective. L’ouvrage nous montre que les organisations de travailleurs demeurent déterminantes et constituent l’une des pistes majeures à explorer afin de repenser l’articulation des mobilisations et l’émancipation sociale à l’ère de la mondialisation néolibérale. –Publisher's description
OCLC: 881869467
Keywords: Labor market; Labor market Québec (Province); Marché du travail Québec (Province); Precarious employment; Precarious employment Québec (Province); Québec; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province); Travail précaire Québec (Province)

Seconds: A Graphic Novel - O'Malley, Bryan Lee (Ballantine, 2014)
The highly anticipated new standalone full-color graphic novel from Bryan Lee O’Malley, author and artist of the hugely bestselling Scott Pilgrim graphic novel series Katie’s got it pretty good. She’s a talented young chef, she runs a successful restaurant, and she has big plans to open an even better one. Then, all at once, progress on the new location bogs down, her charming ex-boyfriend pops up, her fling with another chef goes sour, and her best waitress gets badly hurt. And just like that, Katie’s life goes from pretty good to not so much. What she needs is a second chance. Everybody deserves one, after all—but they don’t come easy. Luckily for Katie, a mysterious girl appears in the middle of the night with simple instructions for a do-it-yourself do-over: 1. Write your mistake 2. Ingest one mushroom 3. Go to sleep 4. Wake anew And just like that, all the bad stuff never happened, and Katie is given another chance to get things right. She’s also got a dresser drawer full of magical mushrooms—and an irresistible urge to make her life not just good, but perfect. Too bad it’s against the rules. But Katie doesn’t care about the rules—and she’s about to discover the unintended consequences of the best intentions. From the mind and pen behind the acclaimed Scott Pilgrim series comes a madcap new tale of existential angst, everyday obstacles, young love, and ancient spirits that’s sharp-witted and tenderhearted, whimsical and wise. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/seconds0000omal
Keywords: Blue-collar work; Comic books; strips; etc; Gender; Graphic novels; Love stories; Man-woman relationships; Pink-collar work; Restaurants; Restaurateurs; Social Class and Equality; United States; Women cooks; Young adult fiction

Bad Time Stories: Government-Union Conflicts and the Rhetoric of Legitimation Strategies - Reshef, Yonatan; Keim, Charles (University of Toronto Press, Scholarly Publishing Division, 2014)
The 1990s and 2000s were especially difficult decades for government–public sector union relations in Canada. Rising costs and growing debts meant that governments were on the lookout for savings, and public sector unions and employees were easy targets for government actions. Bitter conflicts between unions and governments erupted and each labour dispute involved numerous rounds of public rhetoric in which both sides attempted to justify their actions and stigmatize their opponents.In Bad Time Stories, Yonatan Reshef and Charles Keim analyse the language of both parties in order to identify the legitimation strategies at work during government-union conflict. The authors use evidence drawn from newspapers, speeches, parliamentary transcripts, and legal statements in presenting a new framework for understanding the discursive strategies employed by governments and unions in labour disputes.Using a case study and linguistic approach, Bad Time Stories offers a unique perspective on industrial relations and will be of interest to scholars in the areas of business, public policy, and communications, as well to those directly involved in union-management negotiations. – Publisher's description

Autonomie collective et droit du travail. Mélanges en l’honneur du professeur Pierre Verge - Roux, Dominic (Presses de l'Université Laval, 2014)
L’apport du professeur Pierre Verge au droit du travail est remarquable! Ses travaux ont profondément marqué cette discipline et en ont accompagné le développement pendant plus de cinquante ans. Engagé, il occupa dès le début de sa carrière diverses fonctions administratives, dont celle de doyen (Normand). Visionnaire, il se tourna rapidement vers la recherche subventionnée et vers l’interdisciplinarité. Pluraliste, son approche se focalisa sur la multiplicité des sources – juridiques ou non - qui jalonnent sa discipline, élargissant ses horizons de recherche, vers la sociologie, notamment. Joueur d’équipe, il sut transmettre à d’autres, ici même et ailleurs dans le monde, son savoir et son expérience, ce qui se traduit par d’innombrables copublications et collaborations, et autant d’amitiés nouées. Rigueur intellectuelle, érudition et ardeur au travail sont des traits de personnalité connus du professeur Verge. Mais à cela s’ajoutent de belles qualités humaines : générosité, affabilité et modestie caractérisent en effet cet homme, authentique, qui, durant son illustre carrière, influença tant de collègues et d’étudiants. Plusieurs d’entre eux ont donc voulu lui rendre un vibrant hommage et exprimer leur attachement et leur reconnaissance sous la forme de Mélanges. –Publisher's description. Contents: 1 La contribution scientifique de Pierre Verge à l'affirmation et à la recomposition du droit du travail / Guylaine Vallée – 2 Un décanat de développement et de consolidation / Sylvio Normand – Autonomie collective et pluralisme juridique : Georges Gurvitch, Hugo Sinzheimer et le droit du travail / Michel Coutu – 4 Corporatism, Neo-Corporatism, and Freedom of Association / Adrian Goldin – 5 Le syndicat obligatoire au Québec : une contrainte individuelle à la faveur de l'autonomie collective / Pierre Verge, Christain Brunelle, Anne-Marie Laflamme et Doninic Roux – 6 "La convention collective lie tous les salariés ..." mais, sans les ligoter! (art. 67 C.t.) / Me Fernand Morin – 7 La solubilité de la convention collective dans son environnement normatif : quelques réflexions sur une mutation institutionnelle / Louis LeBel – 8 Regulating strikes in essential (and other) services after the “New Trilogy” / Bernard Adell – 9 L'arbitrage de grief et le développement de la spécificité du droit du travail : une contribution reconnue / Denis Nadeau – 10 Embracing collective rights: Unions and the new struggle for relevance and autonomy : A view from the Commonwealth Caribbean / Rose-Marie Belle Antoine –11 Collective autonomy in New Zealand / Paul Roth – 12 Social partners : Autonomy and its limits : A Polish perspective / Michal Sewerynski – 13 Le droit français du travail est-il toujours un droit de protection des salariés? / Jean Pélissier – 14 Les tribunaux judiciaires et les conflits collectifs de travail en Amérique latine / Héctor-Hugo Barbagelata – 15 La détermination des conditions collectives de travail dans l'entreprise au Japon : le règlement intérieur et la modification des conditions de travail / Yasuo Ishil – 16 The Wagner model and international freedom of association standards / Lance Compa – 17 Strike ban for public servants in Germany – an international anachronism / Udo R. Mayer– 18 2019 : autonomie collective, élément clé du travail décent des travailleuses et travailleurs domestiques / Adelle Blackett –19 The new public and private international labour regulations and their implementation experiences / Pablo Lazo Grandi – 20 Organisations nouvelles du travail et représentation collective des travailleurs / Jean-Michel Servais – 21 Repenser les politiques des rapports collectifs de travail à l'ère des entreprises transnationales / Gregor Murray.
OCLC: 904427274
Keywords: Associations; Associations. Syndicats; Droit; Droit international. Travailleurs; Droit. Mlanges (Recueils) Labor laws and legislation. Labor laws and legislation; International. Labor unions; Droit. Travail; Labor laws and legislation. Labor laws and legislation; International. Working class; Law and legislation. Travail; Law and legislation. Working class; Mlanges et hommages; Mlanges et hommages. Droit du travail (droit international); Mlanges et hommages. Syndicats; Mlanges et hommages. Travailleurs; Societies; etc. Droit du travail; Societies; etc. Labor unions

Travail et syndicalisme : origines, évolution et défis d'une action sociale - Thwaites, James D. (James Douglas) (Presses de l'Université Laval, 2014)
D’où vient le syndicalisme ? À quoi répond-il ? Quelles sont ses formes ? De quelle façon agit-il ? Quels sont ses effets ? Quels sont ses défis ? Comment évolue-t-il ? Les 42 textes qui composent cette anthologie proposent diverses réponses à ces interrogations. Les auteurs sélectionnés traitent des aspects les plus significatifs du syndicalisme d’hier, d’aujourd’hui et de demain. Ils représentent neuf disciplines et des positions variées. Le résultat est un foisonnement remarquable d’idées qui pousse à la réflexion, au questionnement et aux remises en cause relativement à ce phénomène qui a des effets multiples sur l’économie, la politique et la société et qui fêtera bientôt ses 200 ans en territoire canadien et québécois. –Résumé de l'éditeur
Keywords: Histoire; Mouvement ouvrier; Relations industrielles; Syndicalisme; Syndicats; Travailleurs

Liberating Temporariness? Migration, Work, and Citizenship in an Age of Insecurity - Vosko, Leah F.; Preston, Valerie; Latham, Robert (McGill-Queen's University Press, 2014)
[E]xplores the complex ways in which temporariness is being institutionalized as a condition of life for a growing number of people worldwide. The collection emphasizes contemporary developments, but also provides historical context on nation-state membership as the fundamental means for accessing rights in an era of expanding temporariness - in recognition of why pathways to permanence remain so compelling. Through empirical and theoretical analysis, contributors explore various dimensions of temporariness, especially as it relates to the legal status of migrants and refugees, to the spread of precarious employment, and to limitations on social rights. While the focus is on Canada, a number of chapters investigate and contrast developments in Canada with those in Europe as well as Australia and the United States. Together, these essays reveal changing and enduring temporariness at local, regional, national, transnational, and global levels, and in different domains, such as health care, language programs, and security. The question at the heart of this collection is whether temporariness can be liberated from current constraints. While not denying the desirability of permanence for migrants and labourers, "Liberating Temporariness?" presents alternative possibilities of security and liberation. –Publisher's description, Contents: Introduction: Liberating Temporariness? Imagining Alternatives to Permanence as a Pathway for Social Inclusion / Robert Latham, Leah F. Vosko, Valerie Preston, and Melisa Bretón. Part 1: Security, Temporary Status, and Rights. Rethinking Canadian Citizenship: The Politics of Social Exclusion in the Age of Security and Suppression / Yasmeen Abu-Laban – Permanent Patriots and Temporary Predators? Post-9/11 Institutionalization of the Arab/Orientalized “Other” in the United States and the Contributions of Arendt and Said / Abigail B. Bakan – Indefinitely Pending: Security Certificates and Permanent Temporariness / Mike Larsen. Part 2: International Organizations and Transnational Dynamics of Temporary Work. Managed Migration and the Temporary Labour Fix / Christina Gabriel – Institutionalizing Temporary Labour Migration in Europe: Creating an “In-between”’ Migration Status / Tesseltje de Lange and Sarah van Walsu – The Permanence of Temporary Labour Mobility: Migrant Worker Programs across Australia, Canada, and New Zealand / Emily Gilbert. Part 3: Temporary Status, Social Welfare, and Marginalization. Brain Circulation or Precarious Labour? Conceptualizing Temporariness in the United Kingdom’s National Health Service / Parvati Raghuram – Language Training and Labour Market Integration for Newcomers to Canada / Eve Haque – Resituating Temporariness as the Precarity and Conditionality of Non-citizenship / Luin Goldring – Constructing and “Liberating” Temporariness in the Canadian Non-profit Sector: Neoliberalism and Non-profit Service Providers / John Shields. Part 4: (Re)Framing Temporariness. Mexican Migrant Transnationalism and Imaginaries of Temporary/Permanent Belonging / Marianne H. Marchand – Temporariness: Other than Permanence, and in the Lives of People - Always… / Deepa Rajkumar – Temporal Orders, Re-collective Justice, and the Making of Untimely States / Robert Latham.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/liberatingtempor0000unse
Keywords: Canada; Foreign workers; Social conditions

La surqualification au Québec et au Canada - Vultur, Mircea (Presses de l'Université Laval, 2014)
La surqualification, définie comme la situation qui caractérise un individu dont le niveau de formation dépasse celui qui est normalement requis pour l’emploi occupé, a subi une forte tendance à la hausse au cours des vingt dernières années. Au Québec et au Canada, elle touche un tiers des travailleurs, surtout les plus jeunes. Ce phénomène, qui témoigne de l’incapacité du marché du travail à offrir à un grand nombre de personnes des emplois qui correspondent à leurs qualifications, est devenu pour tous les acteurs de la vie économique et sociale un enjeu de premier ordre. Ce livre présente un ensemble d’études récentes sur la surqualification. Son objectif est de mesurer l’étendue du phénomène du point de vue statistique et de mettre en relief les facteurs qui interviennent dans sa genèse et son développement. L’ouvrage évalue plusieurs approches et modèles analytiques et présente des résultats de recherches qui utilisent diverses bases de données. Il offre un portrait détaillé de la surqualification au Québec et au Canada. De manière plus fondamentale, il soulève la question de la valeur des diplômes sur le marché du travail et suggère des pistes de réflexion pour atteindre l’adéquation entre la formation de la main-d’œuvre et le profil des emplois. –Publisher's description
https://www.pulaval.com/livres/la-surqualification-au-quebec-et-au-canada OCLC: 872511067
Keywords: Canada; Canada Conditions économiques 1991-; Canada Economic conditions 1991-; Diplômés de l'enseignement supérieur Travail Canada; Economic history; Livres numériques; Québec; Québec (Province); Québec (Province) Economic conditions 1991-; Recueil de contributions (Descripteur de forme); Since 1991; Sous-emploi; Sous-emploi Canada; Sous-emploi Canada Québec (Canada; province) Statistiques; Sous-emploi Canada Statistiques; Sous-emploi Québec (Province); Sous-emploi Québec (Province) Statistiques; Statistics; Statistiques (Descripteur de forme); Underemployment; Underemployment Canada; Underemployment Canada Statistics; Underemployment Québec (Province); Underemployment Québec (Province) Statistics; e-books

Quand travailler enferme dans la pauvreté et la précarité: travailleuses et travailleurs pauvres au Québec et dans le monde - Yerochewski, Carole (Presses de l'Université du Québec, 2014)
Travailler ne met plus à l’abri de la pauvreté et peut enfermer dans la précarité. Car la société salariale est affaiblie par les transformations des interventions entrepreneuriales et étatiques. De plus en plus de travailleurs et, surtout, de travailleuses n’ont plus accès aux protections collectives et sociales qui leur donnaient un appui pour mener des projets professionnels et de vie. L’heure est à la remarchandisation du travail. Pour étayer le phénomène de la pauvreté en emploi et en mesurer l’ampleur au Québec, l’ouvrage propose de nouvelles constructions statistiques qui reposent sur une définition extensive de la notion de travailleur. Le choix de cette définition – définition qui s’accorde avec le caractère multidimensionnel de la pauvreté en emploi – se trouve justifié par les travaux de recherche menés par les membres du Groupe interuniversitaire et interdisciplinaire de recherche sur l’emploi, la pauvreté et la protection sociale (GIREPS). L’ouvrage met en lumière les différents facteurs de développement des formes d’emploi qui enferment dans la pauvreté et la précarité des travailleuses et travailleurs canadiens, résidents ou immigrants temporaires rendus vulnérables par leur position sociale. Il porte un regard à la fois sur les mutations du travail et de l’emploi, sur les transformations des États-providence et sur leur rôle dans l’informalisation du travail et de l’économie, sur les modalités de gestion de la main-d’œuvre par les entreprises ainsi que sur la réactualisation des rapports sociaux de classe, de genre et de race. Il montre que la forte remontée des inégalités socioéconomiques ne résulte d’aucun déterminisme, mais de l’absence ou de la remise en cause des protections légales ou collectives. Il expose comment le retour de la pauvreté en emploi s’inscrit dans la mise en concurrence des travailleurs à l’échelle planétaire. Il se conclut, enfin, sur les formes d’action collective qui interpellent les formes institutionnalisées et nourrissent de nouvelles aspirations et revendications possiblement communes. –Résumé de l'éditeur
https://www.puq.ca/catalogue/livres/quand-travailler-enferme-dans-pauvrete-precarite-2714.html OCLC: 878183400
Keywords: Precarious employment; Precarious employment Québec (Province); Québec; Québec (Province); Travail précaire; Travail précaire Québec (Canada; province); Travail précaire Québec (Province); Travailleur pauvre; Travailleurs pauvres; Travailleurs pauvres Québec (Canada; province); Travailleurs pauvres Québec (Province); Working poor; Working poor Québec (Province)

According to Baba: A Collaborative Oral History of Sudbury's Ukrainian Community - Zembrzycki, Stacey (UBC Press, 2014)
Dreams of steady employment in the mining sector led thousands of Ukrainian immigrants to northern Ontario in the early 1900s. As a child, historian Stacey Zembrzycki listened to her baba’s stories about Sudbury’s small but polarized community and what it was like growing up ethnic during the Depression. According to Baba grew out of those stories, out of a granddaughter’s desire to capture the experiences of her grandparents’ generation on paper. Eighty-two interviews conducted by Stacey and her grandmother, Olga, laid the groundwork for this insightful and deeply personal social history of one of Canada’s most colourful ethnic communities. The interview process also brought to light the challenges of doing collaborative oral history with community members, particularly as Stacey lost authority to her baba, wrestled it back, and eventually came to share it, and as interviewees met questions with nostalgic reminiscences, subversive humour, or impenetrable silence. By providing a realistic glimpse into the hard work that goes into making communities partners in oral history research, this book provides a new paradigm for studying the politics of memory, one that recognizes that people are not passive recipients of their histories but rather counter and create narratives about the past by invoking alternative ways of remembering. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/accordingtobabac0000zemb OCLC: 862781680
Keywords: Biographies; Canadiens d'origine ukrainienne Ontario Sudbury Biographies; Canadiens d'origine ukrainienne Ontario Sudbury Conditions sociales; Canadiens d'origine ukrainienne Ontario Sudbury Entretiens; Canadiens d'origine ukrainienne Ontario Sudbury Histoire; Histoire orale Ontario Sudbury; Interviews; Kanada Ontario Sudbury; Ontario Sudbury (Greater Sudbury); Ukrainare sociala förhållanden; Ukrainian Canadians Ontario Sudbury Biography; Ukrainian Canadians Ontario Sudbury History; Ukrainian Canadians Ontario Sudbury Interviews; Ukrainian Canadians Ontario Sudbury Social conditions; Ukrainians; Ukrainians Ontario Sudbury Biography; Ukrainians Ontario Sudbury Interviews; Ukrainians Ontario Sudbury Social conditions; Ukrainians Social conditions; Zembrzycki; Olga Entretiens; Zembrzycki; Olga Interviews; interviews